VV-ECMO for COVİD-19 related ARDS during pregnancy - ESİM BÜYÜKBAYRAK, ESRA (My University, 2022)
Objectives: Right ventricular (RV) failure following heart transplant (HTx) carries significant morbidity and mortality. When medical therapy becomes ineffective, mechanical circulatory support (MCS) could be lifesaving. Protek Duo (LivaNova) is a recent temporary right ventricular assist device (RVAD). The dual-lumen cannula is inserted percutaneously via right internal jugular vein (IJV) under fluoroscopy and transesophageal echocardiography guidance. The inflow portion is positioned in the right atrium and the outflow tip in the pulmonary trunk, the cannula is then connected to an extracorporeal centrifugal pump (CentriMagTMAbbott) and provides up to 4 L/min in order to unload the RV. Aim of the study was to verify the feasibility and safety of this novel approach in the setting of RV failure after HTx. Methods: Single-center observational retrospective study investigating the use of Protek Duo percutaneous RVAD for RV failure after HTx was conducted from May 2019 to November 2021. Results: Main characteristics are shown in the table. Six patients were included in the study, 66 % had a MCS prior HTx. RVAD was successfully implanted in all patients on a median time of 34[4–53] hours after HTx. All patients were successfully weaned off RVAD after a median of 17[9–26] days. There were no major devicerelated adverse events. None of the patients required conversion to surgical RVAD. 66% developed IJV thrombosis despite adequate anticoagulation therapy. Survival at ICU discharge was 83%, only one patient died due to fungal endocarditis. In-hospital mortality was 17%.
Keywords: KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); PERİFERİK DAMAR HASTALIKLARI; CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); PERIPHERAL VASCULAR DISEASE